La gentrification mise en politiques - Mathieu Van Criekingen (Métropoles)
Following other works, this paper argues that analysing the ongoing development of gentrification processes cannot be detached from the consideration of the supportive role played by public policy. On this basis, this paper first aims at building an analytical framework of gentrification policies that could, on the one hand, make sense of the generalisation of policy actions and instruments supporting gentrification in various urban contexts and, on the other hand, provide insights into the particular socio-spatial and political configurations within which gentrification policies are played out. Gentrification policies are both vehicled by the ongoing neoliberalisation of urban policy frameworks and inserted into situated mobilisations of diverse actors, public and private, operating at different scales. This framework is then empirically tested on the case of the so-called “urban revitalisation” policies conducted in Brussels since the early 1990s. We identify how public policy co-produce gentrification in Brussels, highlighting the social and political bases of gentrification policies, their instruments and their effects. If it is confined to addressing the “side effects” of gentrification – even to deplore them, research would miss the decisive role played by public policy in the co-production of gentrification processes.